MENUJU PENDIDIKAN KATOLIK YANG MEMIHAK ORANG MISKIN - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2018)
Naturally, all mankinds have a desire to know. In this pattern knew that education is the natural need of the human being. This fact encourages the Catholic Church to dedicate his lives for education. This paper will punctuate the option of the Church that the poor and the oppressed must be helped, especially in education. This option, of course, has little popularity, because of its risks. Education is effective evangelization. Meanwhile, as the power and culture of the empire were deteriorating, the Catholic Church was gaining headway, especially among the poor and oppressed masses.